STUDY OF THE CRIME OF TRAFFICKING IN PERSONS ON SHIPPING (PN TUAL DECISION NUMBER 106/PID SUS/2015/PN TUL) - Immanuel Simanjuntak; Silvi Azmi; Daniel Maroloan Nainggolan (Awang Long Law Review, 2022)
The crime of trafficking in persons (human trafficking) is a very complex crime that is difficult to eradicate. In cases of criminal acts of trafficking in persons, usually it does not only involve one area of ​​life but more than one area of ​​life. The practice of trafficking in persons is rife in the world, especially in the world of shipping. The crime of trafficking in persons (human trafficking) is a very complex crime that is difficult to eradicate. In cases of criminal acts of trafficking in persons usually do not only involve one area of ​​life but more than one area of ​​life. The crime of trafficking in persons also often occurs not only in the territory of a country but also outside the territory of a country. However, there is more attention devoted to the case of trafficking in persons in the shipping world. For this reason, this study aims to determine the factors that cause the occurrence of the criminal act of trafficking in persons, the sanctions obtained by the perpetrators in the legal system.